Digital Library Development Strategy at Universitas Muhammadiyah Tapanuli Selatan - Lubis, Efi Amrina; Sundariyati, Dwi; Masruri, Anis (International Journal Software Engineering and Computer Science (IJSECS), 2023)
The advent of Information and Communication Technology (ICT) has significantly transformed library paradigms, shifting from traditional manual systems to digital platforms, a change particularly evident in academic libraries. This study focuses on the University of Muhammadiyah Tapanuli Selatan, aiming to develop a strategic framework for its digital library to enhance services in alignment with the tridharma of higher education. Employing a qualitative, descriptive methodology, the research incorporates both primary and secondary data sources. The analysis involves data reduction, presentation, and conclusion drawing. Results show that the University's library, accessible through Windows and Android applications, has experienced a marked increase in user engagement from 2020 to 2023. However, despite this growth, the development of the digital library requires further enhancement to fully realize its potential and meet user expectations. This study underlines the need for ongoing development strategies in digital libraries to keep pace with technological advancements and evolving user needs.